Technology for social inclusion: The case of electricity access in the Brazilian Amazon - Gómez, M.F.; Sanches-Pereira, Alessandro; Silveira, S. (International Centre for Sustainable Development of Energy, Water and Environment Systems, 2013)
This paper explores the Social Technology concept and analyses how it can support the current Brazilian rural electrification initiative. It addresses the question: ‘can Social Technology principles serve to identify concrete tasks to overcome the challenges of universal access in the Amazon? If so, how can they be effectively incorporated into the current Brazilian rural electrification initiative?’ We conclude with the identification of two concrete actions to achieve universal access in isolated areas. First, the recognition, compilation and systematization of local knowledge are important tasks ahead. Second, effective communication channels and methods are needed to spread local knowledge and support the design, implementation, and operation of innovative solutions. Participatory activities are crucial to enable these concrete actions. We highlight the role of the government at central and local levels for the purpose of setting up the appropriate environment for these changes to happen.